Egg albumin assisted sol-gel synthesis of Eu3+ doped SnO2 phosphor for temperature sensing. (September 2020) - Tian, Xiuying; Zhou, Ting; Wen, Jin; Chen, Zhanjun; Ji, Changyan; Huang, Zhi; Lian, Shixun; Liu, Xin; Peng, Hongxia; Li, Chunyan; Li, Jing; Hu, Jilin; et al.
Graphical abstract: Highlights: Egg albumin assisted sol-gel synthesis of Eu 3+ doped SnO2 phosphor. The concentration quenching mechanism was attributed to the dipole-quadrupole interaction type. SnO2 : 2%Eu 3+ had high relative sensitivity of 3.214 % K −1 at 298 K (2854.42/T 2 K −1 ). A promising phosphor for possible applications in temperature sensing. Abstract: SnO2 : Eu 3+ phosphors were prepared via egg albumin assisted sol-gel method. The typical sample SnO2 : Eu 3+ had tetragonal rutile structure. The sample SnO2 : Eu 3+ had irregular lamellar structure and serious agglomeration. The optical bandgap values of samples were in the range of ∼3.92–4.36 eV. When Eu 3+ concentration was 2.0 %, concentration quenching of dipole-quadrupole (d-q) interaction type occurred. Based on the non-thermally coupled energy level fluorescence intensity ratio, the sample SnO2 : 2%Eu 3+ had the maximum absolute sensitivity of ∼0.87565 K −1 at 373 K. The relative sensitivity was estimated to be 2854.42/T 2 K −1, and the maximum relative sensitivity was 3.214 % K −1 at 298 K, which had great potential application in the field of temperature sensing.